The Effectiveness of the SP4N-LAPOR Application in Managing Public Complaints at the Cirebon Regency Department of Communications and Information Technology - Nira Nurbaetilah; Yanto Heryanto (Journal Of Social Science (JoSS), 2026)
The advancement of information technology has transformed public service delivery, particularly through the implementation of e-government systems aimed at improving transparency, accountability, and efficiency. One such innovation in Indonesia is the SP4N-LAPOR application, which serves as a national platform for managing public complaints. However, its effectiveness at the local government level remains a critical issue. This study aims to analyze the effectiveness of the SP4N-LAPOR application in managing public complaints at the Cirebon Regency Communication and Information Office. This research employed a descriptive qualitative method, utilizing in-depth interviews, observations, and documentation as data collection techniques. Informants include application operators, community members, and IT experts, selected through purposive and accidental sampling. Data analysis follows stages of data reduction, data presentation, and conclusion drawing, with validity ensured through triangulation techniques. The findings reveal that while SP4N-LAPOR has functioned as an integrated complaint management system, its effectiveness is not yet optimal. Challenges include limited public awareness, weak inter-agency coordination, low digital literacy, and technical issues such as system errors. Based on the dimensions of organizational effectiveness goal achievement, integration, and adaptation the system has not fully met its intended objectives. In conclusion, improving effectiveness requires strengthening socialization, enhancing coordination among agencies, and upgrading technical infrastructure to support more responsive and inclusive public services.